2016
DOI: 10.1007/jhep10(2016)095
|View full text |Cite
|
Sign up to set email alerts
|

Holography for N $$ \mathcal{N} $$ = 1∗ on S 4

Abstract: Abstract:We construct the five-dimensional supergravity dual of the N = 1 * mass deformation of the N = 4 supersymmetric Yang-Mills theory on S 4 and use it to calculate the universal contribution to the corresponding S 4 free energy at large 't Hooft coupling in the planar limit. The holographic RG flow solutions are smooth and preserve four supercharges. As a novel feature compared to the holographic duals of N = 1 * on R 4 , in our backgrounds the five-dimensional dilaton has a non-trivial profile, and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
190
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(194 citation statements)
references
References 72 publications
(222 reference statements)
4
190
0
Order By: Relevance
“…As discussed in [4,11,22] this quantity is scheme dependent. One way to obtain a scheme independent observable is to differentiate (2.7) three times with respect to the dimensionless variable ma, see [11,22] for a more detailed discussion.…”
Section: Jhep04(2018)148mentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in [4,11,22] this quantity is scheme dependent. One way to obtain a scheme independent observable is to differentiate (2.7) three times with respect to the dimensionless variable ma, see [11,22] for a more detailed discussion.…”
Section: Jhep04(2018)148mentioning
confidence: 99%
“…One way to obtain a scheme independent observable is to differentiate (2.7) three times with respect to the dimensionless variable ma, see [11,22] for a more detailed discussion. Another interesting set of physical observables computable by supersymmetric localization is given by Wilson loop operators in various representations of the gauge group.…”
Section: Jhep04(2018)148mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, certain theories might have further symmetries, opening up the possibility of localizing the theory. A prominent example of this type is the N = 1 * theory where it was shown that one can obtain unambiguous and scheme independent quantities constructed from the partition function [10]. However, there is no known way to localize an N = 1 theory on S 4 .…”
Section: Jhep07(2017)074mentioning
confidence: 99%
“…Finally, it would be interesting to generalize our calculations to other string solutions in the Pilch-Warner background [4,33,34], to the string dual of the pure N = 2 theory [35,36], where a remarkable match between localization results for Wilson loops and supergravity has been observed [37], and to backgrounds with N = 1 supersymmetry, such as the Polchinski-Strassler background [38] or its S 4 counterpart [39], albeit in this case no fieldtheory predictions are available yet.…”
Section: Jhep04(2017)095mentioning
confidence: 99%